Epigenetic Impacts of Ascorbate on Human Metastatic Melanoma Cells - Venturelli, Sascha; Sinnberg, Tobias W.; Berger, Alexander; Noor, Seema; Levesque, Mitchell Paul; Böcker, Alexander; Niessner, Heike; Lauer, Ulrich M.; Bitzer, Michael; Garbe, Claus; Busch, Christian (Frontiers in Oncology, 2014)
In recent years, increasing evidence has emerged demonstrating that high-dose ascorbate bears cytotoxic effects on cancer cells in vitro and in vivo, making ascorbate a pro-oxidative drug that catalyzes hydrogen peroxide production in tissues instead of acting as a radical scavenger. This anticancer effect of ascorbate is HIF-1α- and O2–dependent. However, whether the intracellular mechanisms governing this effect are modulated by epigenetic phenomena remains unknown. We treated human melanoma cells with physiological (200 µM) or pharmacological (8 mM) ascorbate for 1 h to record the impact on DNA methyltransferase (DNMT)-activity, histone deacetylases (HDACs) and microRNA expression after 12 h. The results were analyzed with the MIRUMIR online tool that estimates the power of microRNA to serve as potential biomarkers to predict survival of cancer patients. FACS cell cycle analyses showed that 8 mM ascorbate shifted BLM melanoma cells towards the sub-G1 fraction starting at 12 h after an initial primary G2/M arrest, indicative for secondary apoptosis induction. In pharmacological doses ascorbate inhibited the DNMT-activity in nuclear extracts of MeWo and BLM melanoma cells, but did not inhibit human HDAC enzymes of classes I, II and IV. The expression of 151 microRNAs was altered 12 h after ascorbate treatment of BLM cells in physiological or pharmacological doses. Pharmacological doses up-regulated 32 microRNAs (≥4-fold) mainly involved in tumor suppression and drug resistance in our preliminary microRNA screening array. The most prominently up-regulated microRNAs correlated with a significantly increased overall survival of breast cancer- or nasopharyngeal carcinoma patients of the MIRUMIR database with high expression of the respective microRNA. Our results suggest a possible epigenetic signature of pharmacological doses of ascorbate in human melanoma cells and support further pre-clinical and possibly even clinical evaluation of ascorbate for melanoma therapy.